Coberturas vegetais e doses de nitrogênio, associadas à inoculação com Azospirillum brasilense, no cultivo do milho na região de Cerrado - Portugal, José Roberto [UNESP] (2015)
In Brazil and in the world, maize crop is one of the most important because it is the basis of animal feed and also used in human feed. Sustainable techniques of management in maize crop are needed, aiming at increasing yield, reducing costs and environmental impacts. The objective of this study was to evaluate different cover crops (millet, sunn hemp, pigeonpea, millet + sunn hemp, millet + pigeonpea and fallow), N rates (0, 40, 80 and 120 kg ha -1 ) with and without inoculation of seeds with Azospirillum brasilense in maize crop, cultivated in no- tillage system on growth and yield in the Cerrado region. The experimental design was complete randomized blocks in a factorial scheme 6x4x2, constituting 48 treatments, with 4 replications. The study was conducted at the Experimental Farm belonging to the Faculty of Engineering - UNESP (Ilha Solteira), located in Selviria - MS. The soil of the place is a Typical Dystrophic Red Latosol clayey texture. The average annual rainfall is 1.330 mm, the average annual temperature is 25°C and the relative humidity between 70 and 80%. During the experiment, the following evaluations were performed: dry matter, content and accumulated values of N, P and K in cover crops; in maize: initial and final population of plants, production of dry matter of the shoots, leaf nitrogen content, leaf chlorophyll index, content and accumulated values of N, P and K in the whole plant, plant height and of ear insertion, stem diameter, ear length, ear diameter, thousand grain weight and grain yield. The cover crops except the pigeonpea in 2012/13 and fallow in 2013/14 produced adequate amount of residue to keep the no-tillage system in the Cerrado region. The consortium of millet + sunn hemp provided the greater accumulated amount of N and K for both years of cultivation. The great yield of maize grains under pigeonpea residue was due to increase in ear diameter and thousand-grain weight. Thus, the great maize yield ...